Eksperimen Teknik Tile Trapping pada Perca Brokat - Ni Luh Nila Febrianti; I Nyoman Artayasa; Gede Pasek Putra Adnyana Yasa (Universitas Negeri Surabaya, 2026)
The increasing amount of brocade and lace scrap waste in the kebaya industry in Bali has become a major environmental problem and an opportunity for sustainable textile material innovation. This study aims to develop textile materials through innovative fabric manipulation techniques with tile trapping techniques and exploration in the use of color combinations, namely analogous, complementary, and monochromatic colors. This study uses a descriptive qualitative approach with an experimental method consisting of three main stages: observation is carried out by identifying the type of brocade, fabric thickness, fabric motif, and size of the brocade scrap. The experiment produced three material prototypes based on the color scheme, then conducted a final evaluation which was carried out visually to assess the appearance aspects of color harmony, motif, texture, neatness of stitching, and material strength. The results show that the tile trapping technique is able to combine brocade scraps with various sizes and fabric motifs into a new textile material that is stable and functional. The analogous color scheme produces a harmonious impression, the complementary color scheme provides a strong visual contrast, while the monochromatic color scheme creates a unified and soft impression. This research contributes to the development of sustainable textile material innovation and supports environmentally friendly fashion practices based on Bali's local potential.